Hubungan Minat Karir dan Pemilihan Karir Peserta Didik SMK N 1 Padang Panjang - Nada Nazhifah (Empowerment Counseling Journal, 2025)
Vocational High Schools (SMK) are formal education mandated by law to prepare human resources ready to enter the workforce and become productive workers. Career choice is a crucial process that reflects an individual's readiness to determine a future direction that aligns with their potential and life goals. Career interest is a person's desire to make choices in carrying out tasks within their field and responsibilities. This study aims to determine whether there is a relationship between career interest and career choice. This study used a quantitative approach with a correlational approach, using a questionnaire as the data collection technique. Respondents were 10th-grade students. The methods used included instrument testing (Validity and Reliability), prerequisite testing (Normality and Linearity), and hypothesis testing (Product Moment Correlation, Chi-Square, and Determination). SPSS 20.0 software was used for analysis. The results of this study indicate that there is a positive and significant relationship between career interest and career choice of students at State Vocational High School 1 Padang Panjang, the alternative hypothesis (H₁) is accepted and the null hypothesis (H₀) is rejected. In addition, the regression results show that career interest contributes 16.9% to career choice. Overall, the analysis results show that career interest has a positive and insignificant relationship with career choice, which is included in the weak category.